STRATEGI KEBIJAKAN LUAR NEGERI RUSIA "THE GREATER EURASIA" TERHADAP ARSITEKTUR KEAMANAN EURASIA PADA PERIODE PEMERINTAHAN VLADIMIR PUTIN - Cindy Larasati (2021)
Under the administration of President Vladimir Putin, Russia formulated the policy "The Greater Eurasia" in order to create a security architecture in Eurasia. The Eurasian region, located between the continents of Europe and Asia, is a vital region and a buffer zone for various interests such as the European Union and the US. The Eurasia region is located on the Russian border and is a former Soviet territory. After the Cold War Western powers increased and its influence began to enter the Eurasia region, Putin as President of Russia called on Russia with its Foreign Policy, The Greater Eurasia which was formalized in 2014. The regional security architecture is in line with the vision of Russia and Russia as a model of global governance.